Parenting Self Efficacy Among Teen Mothers : A Scoping Review - anggit asnea afita; Dewi Rokhanawati; Intan Mutiara Putri (International Journal of Health Science and Technology, 2021)
Parenting self-efficacy (PSE) is the ability of parents to influence children's behavior and development positively. Psychologically, Teen mothers are considered less competent to become parents than adolescents on controlling their emotions and actions. This scoping review aims to review the literature on PSE on teen mothers. This scoping review technique uses the Arskey and O'melley 2005 approach, namely identifying.research. questions,.identifying.relevant.studies, selecting articles, charting.data and compiling,  followed by reporting.results. From 19.articles that have been reviewed, 7 articles describe PSE's success factors and PSE barriers among teen mothers.